Leptin Modulates Allograft Survival by Favoring a Th2 and a Regulatory Immune Profile. Issue 1 (27th September 2012) - Moraes‐Vieira, P. M. M.; Bassi, E. J.; Larocca, R. A.; Castoldi, A.; Burghos, M.; Lepique, A. P.; Quintana, F. J.; Araujo, R. C.; Basso, A. S.; Strom, T. B.; Câmara, N. O. S.
Ob/ob